2011
DOI: 10.1371/journal.pone.0027613
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Monotherapy Increases ACTH and Cortisol Response in the Dex/CRH Test in Unipolar Depressed Subjects. A Study with 30 Treatment-Naive Patients

Abstract: BackgroundDistorted activity of the hypothalamic-pituitary-adrenocortical (HPA) system is one of the most robustly documented biological abnormalities in major depression. Lithium is central to the treatment of affective disorders, but little is known about its effects on the HPA system of depressed subjects.ObjectiveTo assess the effects of lithium monotherapy on the HPA system of patients with major depression by means of the combined DEX/CRH test.MethodThirty drug-naive outpatients with major depression (si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…On the other hand, previous studies have demonstrated that Li administration increased the levels of ACTH and corticosterone in the plasma of rats . Wood and colleagues demonstrated that 36 days of Li treatment did not significantly alter corticosterone levels. The effects of Li on the HPA axis are therefore somewhat controversial.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, previous studies have demonstrated that Li administration increased the levels of ACTH and corticosterone in the plasma of rats . Wood and colleagues demonstrated that 36 days of Li treatment did not significantly alter corticosterone levels. The effects of Li on the HPA axis are therefore somewhat controversial.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have identified an increase in cortisol from baseline after a 12-day period of withdrawal from psychotropic treatment (Naber et al 1985;Albus et al 1985). Unlike antipsychotics, mood stabilisers, including lithium carbonate, have been shown to increase cortisol levels in a dose dependent manner (Platman and Fieve 1968;Bschor et al 2011;Eroglu et al 1979).…”
Section: Levels Of Cortisol In Schizophrenia and Bipolar Disordermentioning
confidence: 99%
“…11 Moreover, it has been demonstrated that Li leads to a significant activation of the hypothalamic-pituitary-adrenal (HPA) system in patients with major depression, rising CRH-stimulated parameters in the DEX/CRH test. 12 Identifying such a Li-responsive gene network in the brain would allow us to distinguish between subsets of genes underlying therapeutic and nontherapeutic actions of Li. The aim of this study was to investigate the potential association of genetic variability at 16 candidate genes related to PI (INPP1, MARCKS, IMPA1, IMPA2, ITPKC, PLCG1), GSK3 (GSK3B, GSK3A, CREB1), HPA (FKBP5, CRHR2, CRHR1), and glutamatergic (GRIA2, GABRB2, GRIK2, GRIK5) systems with Li response in BP.…”
mentioning
confidence: 99%